PENINGKATAN KOMPETENSI PROFESIONAL GURU DALAM MENDUKUNG ERA PEMBELAJARAN 5.0 - Devi Ristyana Puji Lestari; Hartanti , Reni; Harumawati, Dessy Mega; Marpaung, Dian Wahyu; Syafitri, Rizka Malia; Julianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to discuss how the readiness and professional improvement of teachers in the learning era 5.0, one of which is by improving the quality of the competence of the teachers themselves. With the development of science and technology in the global era, it has caused changes in the field of education. The method used to achieve the objectives in this community service activity is a socialization method packaged in educational webinar activities. The implementation of this webinar is carried out online through the Zoom Meeting application. The results of research by distributing questionnaires show that respondents have a good understanding of modern learning concepts, feel competent in designing learner-centered learning, and are ready to apply technology. Collaboration between teachers and organizing webinars are also considered important and useful. This reflects a positive attitude towards innovation and cooperation in improving the quality of education. For this reason, improving and developing the quality/competence of human resources, in this case teachers, is absolutely necessary. Improving and developing teacher competence is a process to improve teachers' abilities, skills and expertise in helping to do their work as educators to welcome the era of society 5.0.